Comparison of various potting media for their influence on nutrients supply, germination, and growth of muskmelon (cucumis melo L.) seedlings. Issue 1 (2nd January 2016) - Mustafa, Ghulam; Ali, Muhammad Arif; Abid, Muhammad; Masood, Sajid; Ahmad, Niaz; Aamer, Muhammad; Qayyum, Muhammad Farooq; Hussain, Sajjad
ABSTRACT: Peat moss is used as potting mix for growing muskmelon ( Cucumis melo L.) seedlings. However, it is not economical for most of the farmers in developing countries. The objectives of the present study were to compare various sources of composts as substitutes for peat moss, evaluate their physicochemical properties, and their effects on germination and growth of muskmelon ( Cucumis melo L.) seedlings under greenhouse conditions. The treatments included pure peat moss (control), and composts prepared from guar ( Cyammopsis tetragonoloba L.), jantar ( Sesbania aculeate L.), and wheat ( Triticum aestivum L) straw, at three air-filled porosity (AFP) levels (10, 15, and 20%) and rice ( Oryza sativa ) hulls at 10% AFP level. The second factor was the addition and devoid of nitrogen (N), phosphorus (P), and potassium (K) fertilizers. The addition of fertilizers in all potting media at 10% AFP level showed a small increase in total nitrogen, extractable phosphorus, and potassium. In the guar and jantar compost at 10% AFP, the values of total N (92.43 and 85.32%), extractable P (68.13 and 76.65%), and K (63.33 and 49%) were higher than in peat moss. It is concluded that composts of guar, jantar, wheat straw, and rice hulls at 10% AFP level can be used as a substitute of peat moss for growing muskmelon seedlings, but the addition of N, P, and K fertilizers is required in wheat straw and rice hulls compost for better nutrition of muskmelon seedlings.